Psychiatric manifestations of Kleefstra syndrome: a case report - Yoshida, Kazunari; Müller, Daniel J.; Desarkar, Pushpal (Frontiers in Psychiatry, 2023)
Background Kleefstra syndrome is a rare genetic condition, which affects at least 1 in 120,000 individuals who have a neurodevelopmental disorder, characterized by the core clinical phenotype of intellectual disability, hypotonia, severe speech delay, and distinct facial characteristics with additional clinical features including sleep disturbance, overweight, psychiatric disorders, and autism spectrum disorder. To date, a limited number of case reports of Kleefstra syndrome with psychiatric manifestations have been reported. Case presentation We reported a case of a 35-year-old male diagnosed with Kleefstra syndrome, who also had diagnoses of autism spectrum disorder and moderate to severe intellectual disability. He exhibited various psychiatric manifestations, including temporarily manic-like symptoms, excessive eating/overweight, addictive/gambling behaviors, inappropriate and unsafe internet use, sleep disturbance, rigid routines, and behaviors that challenged in the form of meltdowns. These symptoms were eventually relatively successfully managed with a combination of non-pharmacological and pharmacological treatments. Conclusion To our knowledge, there is only a limited number of case reports that detail patients with Kleefstra syndrome exhibiting various psychiatric manifestations. Our report adds further knowledge to the paucity of literature and highlights the effectiveness of a combination of non-pharmacological and pharmacological treatments for behavioral/psychiatric difficulties in Kleefstra syndrome.